Altitude measurement of low elevation target in complex terrain based on orthogonal matching pursuit. Issue 5 (1st May 2017) - Li, Cunxu; Chen, Baixiao; Zheng, Yisong; Yang, Minglei
Abstract : In this paper, a novel method is proposed to deal with altitude measurement of low‐elevation target for very high frequency (VHF) radars in complex terrain. In VHF radars, the altitude measurement of low elevation target is unstable and unfavorable owing to the presence of multipath phenomenon. The multipath signal, reflected by the ground, is highly correlated with the direct signal. Moreover, the direct and multipath signal always fall within the same beamwidth. Especially, in complex terrain, the multipath signal is modulated by the rough and irregular reflecting, which results in performance depravation of the exiting direction‐of‐arrival (DOA) estimation methods, and makes the altitude measurement of low elevation target difficult. To resolve this problem, a perturbation multipath propagation model for low‐angle tracking and localization is developed to simulate the echo of the low elevation target in complex terrain, where the effect of irregular reflecting is considered as random amplitude and phase perturbation of the multipath signal. Then a novel method is proposed to resolve the model and estimate the DOA of the low elevation target. Both computer simulations and real data analysis results illustrate that the proposed method can estimate the DOA with higher accuracy in comparison with the existing methods.